The effect of early administration of combined multi-strain and multi-species probiotics on gastrointestinal morbidities and mortality in preterm infants: A randomized controlled trial in a tertiary care unit - Güney-Varal, İpek and Köksal, Nilgün and Özkan, Hilal and Bağcı, Onur and Doğan, Pelin (The Turkish Journal of Pediatrics, 2017)
Necrotizing enterocolitis (NEC) is a gastrointestinal emergency of the neonatal period. The aim of this study was to demonstrate the use of multistrain and multispecies probiotic on gastrointestinal morbidities and mortality. The study was organized as a randomized controlled, prospective study in premature infants (≤32 week and ≤1500 gram). The ready commercial preparations which contain multi-combined probiotics of Lactobacillus rhamnosus (4.1x108 cfu) + Lactobacillus casei (8.2x108 cfu) + Lactobacillus plantorum (4.1x108 cfu) + Bifidobacterium animalis (4.1x108 cfu) together with 383 mg of fructooligosaccharides and 100 mg of galactooligosaccharides as the prebiotic content, was administered enterally to the probiotic group (n=70); control group constituted of 40 preterms. Primary outcomes of the present study were ≥ Stage 2 NEC and the mortality. Secondary outcomes were culture-proven sepsis and days to reach full enteral feeding. All cases of NEC were seen in group 2 as 3.6% (n=4) of all infants. The mortality was found to be 1.4% (n=1) in Group 1 and 22.5% (n=9) in Group 2. The incidence of NEC and the mortality rate were found to be significantly lower in Group 1 (p=0.016, p=0.001, respectively). In Group 1, the NEC-related mortality rate and sepsis-related mortality rate were significantly lower than that of the control group (p=0.046, p=0.023). In this study, we showed that using probiotic strains in combined multistrain and multispecies forms at higher doses and for prolonged duration had positive effects on gastrointestinal complications, sepsis and mortality in premature infants.